Water‐processable, stretchable, self‐healable, thermally stable, and transparent ionic conductors for actuators and sensors - Lee, Junwoo (2020)
For emerging biocompatible, wearable, and stretchable epidermal electronic devices, it is essential to realize novel stretchable conductors with the attributes of transparency, low‐cost and nontoxic components, green‐solvent processbility, self‐healing, and thermal stabililty. Although conducting materials–rubber composites, ionic hydrogels, organogels have been developed, no stretchable material system that meets all the outlined requirements has been reported. Here, a series of P(SPMA‐r‐MMA) polymers with different ratios of ionic side chains is designed and synthesized, and it is demonstrated that the resulting stretchable ionic conductors with glycerol are transparent, water processable, self‐healable, and thermally stable due to the chemically linked ionic side chain, satisfying all of the aforementioned requirements. Among the series of polymer gels, the P(SPMA0.75‐r‐MMA0.25) gel shows optimum conductivity (6.7 × 10−4 S cm−1), stretchability (2636% of break at elongation), and self‐healing (98.3% in 3 h) properties. Accordingly, the transparent and self‐healable P(SPMA0.75‐r‐MMA0.25) gels are used to realize thermally robust actuators up to 100 °C and deformable and self‐healable thermal sensors.